Adrenal Insufficiency Presenting as Pulseless Ventricular Tachycardia - Hussain, Asraf (Journal of National Heart and Lung Society Nepal, 2024)
Adrenal insufficiency (AI) is a severe sickness induced by adrenal gland or hypothalamic-pituitary-adrenal (HPA) axis dysfunction. It can induce a variety of symptoms, the most serious of which are potentially fatal adrenal crises. This case report describes a clinical scenario involving a 42-year-old male patient who had previously had brain tumor surgery. The patient had presented with fever and gastrointestinal symptoms. He developed pulseless ventricular tachycardia on day two of admission. Patient was promptly treated with electrical cardioversion. Workup revealed QT prolongation on ECG and adrenal insufficiency. Both the patient’s arrhythmias and QT prolongation on ECG responded to intravenous hydrocortisone.